On Modeling of Spray G ECN Using ROI-Based Eulerian-Lagrangian Simulation - Ailaboina, Akhil; Saha, Kaushik (Frontiers in Mechanical Engineering, 2022)
A numerical study has been carried out to understand the effect of Unsteady Reynolds Averaged Navier-Stokes (URANS) (standard 𝑘 ― 𝜀 and RNG 𝑘 ― 𝜀 model) and large eddy simulations (LES) on a multi-hole gasoline direct injection (GDI) fuel injector. The fuel injector considered in this study is the Spray G nozzle from the Engine Combustion Network (ECN). To initiate the simulation rate of injection (ROI) profile is used and a blob injection model is considered in this study. The simulations with standard 𝑘 ― 𝜀 turbulence model, is tuned with the C_ε1 model constant to match the experimental data of liquid and vapor penetrations. The KH breakup model time constant (B_1) and RT breakup length constant 〖(C〗_bl) are tuned for the RNG 𝑘 ― 𝜀 turbulence model. It is observed that by increasing the breakup length model constants 〖(C〗_bl), the radial dispersion of the spray increases, and the extent of the breakup is lowered. Parametric studies are carried out using the different LES sub-grid models. The simulated results are compared in terms of spray penetration, gas axial velocity, and local droplet diameter at 15 mm downstream of the injector tip. The parametric study was also performed by including the geometry of the stepped holes in the computational domain. The ROI-based simulation is initiated at the end of the smaller hole. The case including the stepped holes led to over-prediction compared to the case with the usual computational domain (i.e., without the stepped holes), in terms of spray penetrations. Finally, parametric studies are carried out to understand the relative importance of the individual spray sub-models and the results are conclusive that for a spray simulation both the breakup and evaporation models are dominant and they will help in the understanding of charge preparation mixture in a combustible environment.